2019
DOI: 10.1007/s00520-019-05016-4
|View full text |Cite
|
Sign up to set email alerts
|

MASCC recommendations on the management of constipation in patients with advanced cancer

Abstract: Care in Cancer formed a subgroup to develop evidence-based recommendations on the management of constipation in patients with advanced cancer Methods: These recommendations were developed in accordance with the MASCC Guidelines Policy. A search strategy for Medline was developed, and the Cochrane Database of Systematic Reviews and the Cochrane Central Register of Controlled Trials were explored for relevant reviews / trials respectively. The recommendations were categorised by the level of evidence, and a "cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 58 publications
0
25
0
1
Order By: Relevance
“…Many large-scale and small-scale clinical studies have been performed to evaluate whether chronic constipation increases the risk of intestinal cancer (20). The results of these studies are conflicting and some studies show that constipation raises the risk of cancer and other studies conclude that there is no such risk, and some studies have even shown that chronic constipation can reduce the risk (21)(22)(23)(24). Many studies in this area are on people with cancer in comparison with those who do not have cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Many large-scale and small-scale clinical studies have been performed to evaluate whether chronic constipation increases the risk of intestinal cancer (20). The results of these studies are conflicting and some studies show that constipation raises the risk of cancer and other studies conclude that there is no such risk, and some studies have even shown that chronic constipation can reduce the risk (21)(22)(23)(24). Many studies in this area are on people with cancer in comparison with those who do not have cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment algorithm was based on a review of the literature, which was the basis of recent international guidelines. 11 The original sample size was pragmatic (150 participants), which represented 15% of participants in the feeder study, 3 although we were unsure of the prevalence of OIC in the feeder study (as defined by the Rome IV criteria for OIC). It should be noted that the sample size of the feeder study was based on the prevalence of OIC suggested by an Expert Working Group of European Association of Palliative Care.…”
Section: Methodsmentioning
confidence: 99%
“…International guidelines universally recommend that cancer patients commenced on opioid analgesics should be routinely coprescribed conventional laxatives 9 10 or possibly other treatments to manage constipation. 11 Surprisingly, there is little evidence to support this strategy or indeed to guide the choice of treatment. 11 Even more surprisingly, previous studies have reported frequent non-adherence to these clinical guidelines, 12 and equally lack of adoption/utilisation of new treatments (eg, PAMORAs).…”
Section: What Is Their Significance?mentioning
confidence: 99%
See 2 more Smart Citations